Voluntary carbon disclosure and the cost of equity capital: Empirical evidence from the United Kingdom - Yang, Yue (2022)
This study investigates the correlation between voluntary carbon disclosure and the cost of equity capital in the UK setting. The panel dataset employed covers all FTSE350 companies from 2015 to 2019. We conduct Ordinary Least Squares (OLS) regression and Fixed-effect regression to test the association between voluntary carbon disclosure and the cost of equity. We find that voluntary carbon disclosure proxied by Carbon Disclosure Score (CDS) is negatively related to the cost of equity capital. It reveals that firms’ superior quality disclosure of carbon information could contribute to a lower cost of equity capital. Overall, we suggest that corporate voluntary carbon disclosure has negative effects on the cost of equity capital. This finding provides insights to regulators, managers, and investors in terms of the positive economic implication of voluntary carbon disclosure. Besides, it motivates corporates to proactively disclosure higher quality carbon information.